Epidemiology of chronic lymphocytic leukaemia in an Irish subpopulation with total case ascertainment: an additional tool for health economic planning - Vandenberghe, Elisabeth; Mc Elligott, Tony (My University, 2021)
Chronic lymphocytic leukaemia (CLL) and small lymphocytic lymphoma (SLL) is the commonest B-cell malignancy affecting Caucasians, with a variable national incidence depending on the ethnic composition and age profile of the population.1 The National Cancer Registry of Ireland (NCRI) quotes a Republic of Ireland (ROI) CLL incidence of 6·1/100 000, which appeared lower than our clinical experience indicated.2 Establishing accurate CLL incidence figures and numbers of patients requiring therapy would improve health service provision planning. Chronic lymphocytic leukaemia is a clinically variable disease; up to one-third of patients are never treated, while ‘high-risk’ patients require costly, prolonged targeted therapy to circumvent chemoresistance.3-5 Although unmutated immunoglobulin variable heavy chain (IgVH), tumour protein p53 (TP53), splicing factor 3B subunit 1 (SF3B1), baculoviral IAP repeat-containing 3 (BIRC3) and Notch receptor 1 (NOTCH1) gene mutations confer inferior outcomes, the commonly used targeted therapies that include Bruton tyrosine kinase inhibitors such as ibrutinib and the B-cell lymphoma 2 (BCL2) inhibitor, venetoclax are only available for TP53-disrupted (mutation or deletion) and relapsed CLL.6, 7 The high cost of these drugs is challenging for healthcare budgeting because of the requirement for long-term treatment until toxicity/resistance and the potential for multiple targeted drug combinations. The present study uses a subpopulation ‘complete ascertainment’ approach to define the incidence of CLL and the numbers of patients requiring treatment annually in the ROI, many of whom may benefit from targeted-therapy treatment in first and second line as being defined by recently completed or ongoing studies.
PUBLISHED
Keywords: Ageing; Cancer; Genes & Society; Immunology, Inflammation & Infection; Anticancer therapies; CANCER TREATMENT; CANCER-PATIENTS; Chronic Lymphocytic Leukaemia; Epidemiology; Health outcomes; LEUKAEMIA